The seafood markets in the Northern Mediterranean countries - Paquotte P.; Guillard V. (Marketing of aquaculture products, 1996)
A brief survey of the sea-food markets for the northern Mediterranean countries is presented, i.e. for Cyprus, France, Greece, Italy, Portugal, Spain and Turkey. Then a comparative study between the markets belonging to the European Union is completed. Three of these countries (France, Italy and Spain) are characterized by a huge deficit in their external sea-products trade. Greece is almost balanced, but Portugal has been importing increasingly more over the last few years. About 45 per cent of the imports come from the European Union. After many years of increasing value, we can now see a stabilization in the fish price. Since 1977, the consumption of fresh products has been receding in favour of frozen and processed products. Cultured salmon and shrimp which were less popular a few years ago are now two of the most important sea food items, especially in France, which indicates that these markets are eager to consume products from aquaculture. The distribution channels are still traditional for fresh fish in these countries except in France where supermarkets account for more than 50 per cent of retail sales. The difficulty of gathering homogeneous and reliable information reveals the importance of implementing a network devoted to this data.
Seminar of the CIHEAM Network on Socio-economic and Legal Aspects of Aquaculture in the Mediterranean (SELAM), 1995/10/11-13, Thessaloniki (Greece)